Government Anticipation in Tackling Crime of Money Laundering (White Collar Crime) in Indonesia - Sunarno Edy Wibowo (AIBPM Publisher, 2018)
Indonesia is currently racing with time related to the increasingly rampant criminal corruption committed by state officials who have a very significant impact also on the increase of TPPU. One of the perpetrators' efforts to avoid him from the law by hiding or obscuring his crime through money laundering takes advantage of the mechanism of financial traffic. Money laundering practices are very often committed against money earned from crime. The practice is simply a way to disguise or conceal the proceeds of a criminal offense. Money laundering is then used as a shield for the proceeds of the crime. Therefore, the existence of provisions or regulations on TPPU is very beneficial to minimize the velocity of funds from the crime. The latent danger of corruption has touched almost all levels of society, not only in relation to state organizers, power and policy, but also to the presence of private parties. Various methods have been taken to eradicate it, both preventively and repressively as well as by making changes to the method of eradication. One of the objectives of repressive action is to restore the State's losses. Corruption has resulted in heavy losses to the state's finances and undermines the stability of the national economy. The state losses in the form of assets resulting from corruption in returning it are not easy, the complexity of the settlement of criminal cases is one of the most dominant causes, not to mention the settlement of cases of corruption, especially those that have obtained permanent legal force, in relation to the spoils and payments replacement money, suspects, defendants, or convicted persons who disappeared at the time the proceedings were underway. The handling of TPPU cases has significance for the return of state assets related to the eradication of corruption. Property becomes a very fundamental object in relation to corruption and TPPU. Money laundering is always associated with property derived from a crime. The outcome of corruption is certainly related to assets or property acquired in an unauthorized and dirty manner. The prosecution of the perpetrators of corruption is not only related to the problem of his actions but also the repression of the result of his act of seizure of assets or assets of the perpetrator. Presidential Instruction Number 5 of 2004 on the Acceleration of Corruption Eradication issued by the President on December 9, 2004 to prove the seriousness of the government in criminalizing the money laundering of corruption results as well as a legal instrument that ordered law enforcement officers to immediately restore the state loss (asset recovery).1 The handling of TPPU, is a tough task for PPATK, especially to detect the occurrence of TPPU and further criminal acts. So the prevention and eradication of money laundering requires a systematic and comprehensive mechanism, which includes the detection process and legal process.2 The practice of money laundering through bank mechanisms is possible because banks are the most vulnerable financial institutions, and are subjected to the practice of Money Laundering whereby banks have a clearing system, international correspondence and a secret banking system.3 The role of the financial and government industry (PPATK) in preventing and eradicating TPPU becomes a barometer. It is based on banking and other financial services providers as front lines, in anti money laundering regimes. It is expected that financial institutions together with employees are at the forefront, in an effort to combat illegal financial activities.4